Implementation of Clean and Healthy Living Behavior (PHBS) in Household Arrangement - Indah Sulistyowati (GLOBAL HEALTH SCIENCE GROUP, 2022)
The degree of health is one of the most important elements in efforts to increase the Human Development Index (HDI) of the Indonesian nation. In this case, the degree of health is not only determined by health services, but what is more dominant is environmental conditions and the behavior of the community itself. One of the efforts to improve people's behavior in order to support the improvement of health status can be done through the Clean and Healthy Life Behavior (PHBS) development program. The purpose of this study is to determine the effect of knowledge with the application of clean and healthy living behavior (PHBS) in household settings. This type of research is observational with an analytical survey research method. The population in this study is the household structure in RW 03, Ngijo Village, Gunung Pati District, Semarang City. The sample in this study were all household arrangements in RT 07 RW 03, Ngijo Village, Gunung Pati District, Semarang City, a total of 42 respondents. Data collection by using a questionnaire. Analysis of the relationship between two variables using the Chi-Square test. From the results of the study, it was found that most of the respondents had good knowledge about PHBS, namely 35 people (83.3%) and most of them applied clean and healthy living behavior in household settings, namely 22 household (52.4%). From the results of data analysis using Chi Square statistical test, the value of value = 0.167 > 0.05. it is said that Ha is rejected, which means that there is no influence of knowledge about PHBS on the Application of Clean and Healthy Life Behavior. Suggestions that can be given are the need for guidance and implementation of PHBS materials where this is the key in efforts to improve the quality of public health.